Marketing Strategy of Sumbawa Forest Honey in Sumbawa Regency - Wijayanti, Nila; Mastar, Syahdi; Nurwahidah, Siti (Badan Penerbitan Fakultas Pertanian, Universitas Bengkulu, 2023)
Marketing strategy is needed in developing original products. Sumbawa forest honey is an original product from West Nusa Tenggara, Indonesia. The problems marketing are fluctuating price and the availability of other honey product as competitors. The purpose of this research was to identify the top priorities strategy marketing of this honey. The data analysis using A’WOT. It’s combination of SWOT and AHP analysis. SWOT analysis was employed to identify strengths, weaknesses, opportunities, and threats in marketing of Sumbawa forest honey. AHP (Analitycal Hierarchy Process) analysis was performed to determine priority on alternative of marketing strategy of Sumbawa forest honey. The finding of this research showed that SO strategy was the top priority strategies in marketing of Sumbawa forest honey with value 0.580. The top three priorities on alternative of strategies are packaging the Sumbawa forest honey hygienically and attractively (0.343), maintains the quality and purity of Sumbawa forest honey (0.275), and partnering with financial institutions (0,125).